Effects of Cardiopulmonary Bypass Surgery on Auditory Function: A Preliminary Study. (29th August 2013) - Munjal, Sanjay Kumar; Malik, Parul; Sharma, Anuradha; Panda, Naresh Kumar; Thingnum, Shyam K. Singh
Abstract : Hearing loss has been reported as a complication following cardiac surgery with extracorporeal circulation. Preoperative hearing testing is not commonly done in these procedures, so preoperative and postoperative hearing loss, if any, may occur unnoticed. 30 subjects in the age range of 50–70 with a mean age of 60.16 years with myocardial infarction and scheduled to undergo cardiopulmonary bypass surgery underwent detailed audiological assessment comprising of pure tone audiometry with extended high frequency audiometry, speech audiometry and otoacoustic emissions (OAE) testing. The audiological testing was done preoperatively and at 2 weeks after the surgery. On pure tone audiometry, the difference between pre- and postsurgery mean values for both ears at 10, 12, and 16 KHz showed highly significant differences (P < 0.0001 ). On OAE testing, a significant difference (P < 0.05 ) between pre- and postvalues of signal to noise ratio (SNR) was found. It is hypothesised that CPB surgery makes blood redistribution to other organs easy, deviating from internal ear, which is highly susceptible as it lacks collateral circulation and its cells have high energy metabolism. Epithelial damage on internal ear microcirculation causes reduction of the cochlear potentials and hence hearing loss.